2016
DOI: 10.1111/evo.13108
|View full text |Cite
|
Sign up to set email alerts
|

Impact of cryptic female choice on insemination success: Larger sized and longer copulating male squid ejaculate more, but females influence insemination success by removing spermatangia

Abstract: In polyandrous mating systems, sperm competition and cryptic female choice (CFC) are well recognized as postcopulatory evolutionary forces. However, it remains challenging to separate CFC from sperm competition and to estimate how much CFC influences insemination success because those processes usually occur inside the female's body. The Japanese pygmy squid, Idiosepius paradoxus, is an ideal species in which to separate CFC from sperm competition because sperm transfer by the male and sperm displacement by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 51 publications
0
27
0
Order By: Relevance
“…The occurrence of cryptic female choice is often more difficult to infer due to the diversity of possible underlying mechanisms and their interactions with sperm competition (reviewed by Firman, Gasparini, Manier, & Pizzari, ). Consequently, evidence of cryptic female choice in decapods is limited, but compelling examples of the phenomenon come from studies of other marine species with external sperm deposition (e.g., Japanese pygmy squid, Idiosepius paradoxus ; Sato, Yoshida, & Kasugai, ) and external fertilization (ocellated wrasse, Symphodus ocellatus ; Alonzo, Stiver, & Marsh‐Rollo, ). Cryptic female choice has been proposed in decapods based on behavioral observations, including failed copulations (Bauer, ; Diesel, ; Ra'anan & Sagi, ) and delayed oviposition (Thiel & Hinojosa, ).…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of cryptic female choice is often more difficult to infer due to the diversity of possible underlying mechanisms and their interactions with sperm competition (reviewed by Firman, Gasparini, Manier, & Pizzari, ). Consequently, evidence of cryptic female choice in decapods is limited, but compelling examples of the phenomenon come from studies of other marine species with external sperm deposition (e.g., Japanese pygmy squid, Idiosepius paradoxus ; Sato, Yoshida, & Kasugai, ) and external fertilization (ocellated wrasse, Symphodus ocellatus ; Alonzo, Stiver, & Marsh‐Rollo, ). Cryptic female choice has been proposed in decapods based on behavioral observations, including failed copulations (Bauer, ; Diesel, ; Ra'anan & Sagi, ) and delayed oviposition (Thiel & Hinojosa, ).…”
Section: Discussionmentioning
confidence: 99%
“…Sato et al (2016) suggest that female preference for small male body size and long ejaculation duration demonstrate CFC and not sperm competition because they are female-driven choices. However, Sato et al (2016) found that CFC did not strongly influence final male paternity, suggesting that while females may bias the spermatangia of some males, male-driven sperm competition may still play a role in this system. Sato et al conclude that female preference for small males may have arisen in the Japanese pygmy squid to counter the large volume of spermatozoa produced by large males.…”
mentioning
confidence: 92%
“…The team found that female squid preferentially removed the spermatangia of larger males who copulated quickly-a surprising result after a previous study found that females preferentially removed spermatangia from larger males who copulated for a long time (Sato et al 2014b). Sato et al (2016) suggest that female preference for small male body size and long ejaculation duration demonstrate CFC and not sperm competition because they are female-driven choices. However, Sato et al (2016) found that CFC did not strongly influence final male paternity, suggesting that while females may bias the spermatangia of some males, male-driven sperm competition may still play a role in this system.…”
mentioning
confidence: 92%
See 2 more Smart Citations